EDUKASI PENGGUNAAN MASKER DAN HANDSANITIZER SEBAGAI UPAYA PREVENTIF TERHADAP COVID 19 DI CHECK POIN MESJID AL-MUNA KECAMATAN CILAWU - Mamay; Esa Risi Suazini; Lina Humaeroh; Eldessa Vava Rilla (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
At the end of 2019, the world was shocked by the massive attacking corona virus known as COVID-19. The disease is caused by this virus in a seafood market in Wuhan and has spread to 65 countries. This sharp increase in cases requires preventive efforts that must be carried out by all parties. The spread of this virus can be reduced by using masks and hand sanitizer. Public transportation is a potential place for virus transmission because it comes into contact with large crowds. Community service is carried out as an effort to increase the awareness of public transportation users passing through the check points of the Al-Muna Mosque in Cilawu District to use hand sanitizers and masks as a preventive effort against COVID-19. The result of community service was the achievement of donations of masks and hand sanitizer along with one-by-one educational presentation regarding the prevention of transmission of COVD 19 to vehicle users, both private and public vehicles. Community service has achieved the target, namely the provision of masks and hand sanitisers along with understanding the use and socialization of prevention of COVID-19 to at least 100 people. Vehicle users respond very well with performance indicators, namely they immediately wear a mask and a hand sanitizer according to their function